Vratārka bhāṣā : arthāt vrata nirṇaya pūjā vidhi aura udyāpana bhāṣā ulthā aura kathāoṃ kā mūla Saṃskr̥ta aura bhāṣā ṭīkā sahita - Śaṅkarabhaṭṭa (Son of Nīlakaṇṭha) (Navalakiśora, 1881)
Manual, with votive tales, for Hindu vratas (vows)